2023
DOI: 10.3389/fendo.2023.1139303
|View full text |Cite
|
Sign up to set email alerts
|

Insulin, dibutyryl-cAMP, and glucose modulate expression of patatin-like domain containing protein 7 in cultured human myotubes

Abstract: Expression of patatin-like phospholipase domain containing protein 7 (PNPLA7), also known as neuropathy target esterase-related esterase (NRE), a lysophospholipase, increases with fasting and decreases with feeding in mouse skeletal muscle, indicating it is regulated by insulin, counterregulatory hormones, such as glucocorticoids and catecholamines, and/or nutrients. In cultured mouse adipocytes insulin reduces Pnpla7 expression, underscoring the possibility that insulin regulates PNPLA7 in skeletal muscle. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In one of our studies (100), we found that knocking down the mRNA of PNPLA7 in cultured human myoblasts significantly reduces the α1-subunit of Na + K + -ATPase, acetyl-CoA carboxylase, phosphorylated forms of the 70 kDa ribosomal S6 kinase, and ribosomal protein S6, which suggests that PNPLA7 is important for the function of human myoblasts in a number of aspects (100). Several studies (101−103) in which PNPLA7 was knocked down have confirmed the biological importance of PNPLA7 in energy metabolism and its role in the development of metabolic disorders.…”
Section: Pnpla7 (Ec 3115)mentioning
confidence: 82%
See 1 more Smart Citation
“…In one of our studies (100), we found that knocking down the mRNA of PNPLA7 in cultured human myoblasts significantly reduces the α1-subunit of Na + K + -ATPase, acetyl-CoA carboxylase, phosphorylated forms of the 70 kDa ribosomal S6 kinase, and ribosomal protein S6, which suggests that PNPLA7 is important for the function of human myoblasts in a number of aspects (100). Several studies (101−103) in which PNPLA7 was knocked down have confirmed the biological importance of PNPLA7 in energy metabolism and its role in the development of metabolic disorders.…”
Section: Pnpla7 (Ec 3115)mentioning
confidence: 82%
“…Furthermore, it is suppressed by insulin in the 3T3-L1 adipocytes. A recent study with cultured human myotubes ( 100 ) has shown that insulin suppresses mRNA expression in physiological conditions and dibutyryl-cAMP in the fed state and that PNPLA7 protein levels inversely correlate with glucose concentrations. All this suggests that PNPLA7 is regulated by the nutritional status and plays a role in energy metabolism.…”
Section: Pnpla7 (Ec 3115)mentioning
confidence: 99%
“…Of note, among the genes associated with three enriched GO terms related to catabolic processes, Pnpla2, Samd4b, Tmem259, and Pcbp4 were upregulated by 12-hour MV and downregulated by ES. Pnpla7, the gene whose expression was most altered by 12-hour MV, regulates skeletal muscle energy metabolism by inversely correlating with insulin 33 . Therefore, ES might counteract the catabolic process caused by 12-hour MV.…”
Section: Discussionmentioning
confidence: 99%